Nitrogen maintenance requirements and potential for nitrogen retention of pullets in growth phase - Soares, Leticia [UNESP]; Sakomura, Nilva Kazue [UNESP]; Paula Dorigam, Juliano Cesar de; Liebert, Frank; Nascimento, Mariana Quintino do [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP] (Wiley-Blackwell, 2019)
Experiments were conducted to estimate daily N maintenance requirements (NMRs) and the genetic potential for daily N retention (NRmaxT) of pullets in growth phase. Three nitrogen balance trials were conducted, and a total of 48 Hy-line W-36 pullets were used in each trial in age periods (starter: 14-28, grower: 56-70 and developer: 98-112 days). The treatments consisted of six graded levels of nitrogen in the diets (L1 = 8, L2 = 16, L3 = 24, L4 = 32, L5 = 40 and L6 = 48 g N/kg of feed), formulated using the dilution technique. The regression analyses between nitrogen intake and nitrogen excretion were performed to fit the exponential function and to determine the NMR. The daily NMRs that were estimated at 294, 331 and 355 mg/BWkg0.67 for the initial, grower and developer periods, respectively, were applied for further calculation of NRmaxT as the threshold value of the function between N intake and daily N balance. The NRmaxT was estimated by a statistical procedure following several iteration steps by the Levenberg-Marquardt algorithm until the sum of the squares of the residual was minimized. The NRmaxT was estimated at 3,200, 2,633 and 1,826 mg/BWkg0.67 for starter, grower and developer periods respectively. The determined model parameters were the precondition for modelling of the amino acid requirement based on an exponential N-utilization model and depended on performance and dietary amino acid efficiency. This procedure will be further developed and applied in the subsequent study.
Keywords: growth potential; nitrogen balance; nitrogen utilization model; pullets